Aggregatibacter actinomycetemcomitans LPS binds human interleukin-8 - Ahlstrand Tuuli; Kovesjoki Laura; Maula Terhi; Oscarsson Jan; Ihalin Riikka (Taylor & Francis, 2022)
Various gram-negative species sequester host cytokines using outer membrane proteins or surface modulation by sulfated polysaccharides. An outer membrane lipoprotein (BilRI) of the periodontal pathogen Aggregatibacter actinomycetemcomitans binds several cytokines, including interleukin (IL)-8. Because IL-8 is positively charged at physiological pH, we aimed to determine whether IL-8 interacts with negatively charged lipopolysaccharide (LPS). Binding was investigated using electrophoretic mobility shift assays and microwell-based time-resolved fluorometric immunoassay. LPS from each tested strain of A. actinomycetemcomitans (N = 13), Pseudomonas aeruginosa (N = 1) and Escherichia coli (N = 1) bound IL-8. The Kd value of the A. actinomycetemcomitans LPS-IL-8 interaction varied between 1.2–17 μM irrespective of the serotype and the amount of phosphorus in LPS and was significantly lower than that of the BilRI-IL-8 interaction. Moreover, IL-8 interacted with whole A. actinomycetemcomitans cells and outer membrane vesicles. Hence, LPS might be involved in binding of IL-8 to the outer membrane of A. actinomycetemcomitans. This raises an interesting question regarding whether other gram-negative periodontal pathogens use LPS for IL-8 sequestering in vivo.